Effects of tricarballylic acid on phase transformation of calcium sulfate hemihydrate to the dihydrate form - SAYAN, PERVİZ; POLAT, SEVGİ (WILEY-V C H VERLAG GMBH, 2017)
Phase transformation of calcium sulfate hemihydrate to calcium sulfate dihydrate was performed in a batch-type crystallizer at 20 degrees C in the absence and then the presence of tricarballylic acid. Three different tricarballylic concentrations 250 ppm, 1000 ppm and 2500 ppm were used throughout the experiments. The influence of tricarballylic acid used as an additive on the phase transformation was explored by conductivity measurements. During the transformation process, the crystal water content and crystal structure of the samples were also investigated via SEM, XRD, and TGA analyses. Whereas the crystals obtained in pure media had a plate-like crystal structure, a change in crystal structure occurred in the presence of the additive. Furthermore, the activation energy of the samples was determined using three free kinetic modelling methods: Friedman, Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose. The values of average activation energy ranged from 34.12 to 42.8 kJ/mol in pure media, but this value increased to 51.28 to 55.40 kJ/mol in the presence of the additive. Therefore, TGA-FTIR-MS analyses were carried out to determine whether the tricarballylic acid was adsorbed on the surface of the crystals. The TGA-FTIR result was consistent with the TGA-MS result, confirming that the carboxylic acid was adsorbed on the crystals.
Keywords: calcium sulfate hemihydrate; tricarballylic acid; kinetic models; TGA-FTIR-MS; FGD GYPSUM; KINETICS; CRYSTALLIZATION; DEHYDRATION; MECHANISM; CRYSTALS